NEW MEDIA, CAPACITY-BUILDING IN AFRICA AND CHALLENGES: AN ANALYSIS IN DEPENDENCY - NWOYE, Kenneth O (Socialscientia: Journal of Social Sciences and Humanities, 2018)
The New Media has become increasingly relevant in this age of globalization. This is because there is very little we can do without recourse to Digital Network. In Africa, a lot has been said and done to underline the critical role of New Media in sustainable development and good governance. This paper explores the key challenges of New Media in relation to Capability-Building in Sub-Saharan Africa. The central thesis of the paper is that a lot of obstacles still stand in the way of Capacity-Building in the continent and that the New Media has not been properly and effectively deployed as a veritable platform for sustainable development. The paper concludes by pointing out realistic steps that needs to be taken to address these challenges in the short and long run.